Republic of Moldova : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Moldova's Economic Growth and Poverty Reduction Strategy Paper (EGPRSP) covering 2004-06. The EGPRSP has the potential to become an effective tool for continuous strategic planning, and for providing for the prioritization of strategic objectives and the implementation of related actions. It is also a tool for efficient and transparent allocation of available resources, and for the harmonization of medium- and long-term objectives. The EGPRSP also represents a framework for the coordination of sectoral strategies, directing them toward the accomplishment of the higher-level EGPRSP objectives.